2020
DOI: 10.1002/ejlt.201900261
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Effect Potential of Garlic In Vitro and Real Food System: Effects of Garlic Supplementation on Oxidation Stability and Sensory Properties of Butter

Abstract: In this research, the effect of adding garlic and synthetic antioxidant to butter produced on both quality characteristics and oxidation stability during the storage (1st, 15th, 30th, 45th, 60th, 75th, and 90th days) process is investigated. With this aim, two replicates of butter samples as control, containing different proportions of garlic (butter treated with 2.5%, 5%, 7.5%, 10% crushed garlic) and with 50 ppm butylated hydroxytoluene (BHT) added are prepared. 2,2′‐Azinobis‐(3‐ethylbenzthiazoline‐6‐sulfona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…In general, the concentration and type of additives and flavourings of plant origin to food has a great impact on its sensory acceptance by consumers. In line with the present study, in a study, 10% garlic was added to butter and the results showed that it is not desirable in terms of sensory properties (Aydın and Tahmas Kahyaoğlu 2020). Another study found that the sensory scores of the ghee samples incorporated with 4.0, 6.0 and 8.0% orange peel powder extract were not in the acceptable range (Asha et al .…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In general, the concentration and type of additives and flavourings of plant origin to food has a great impact on its sensory acceptance by consumers. In line with the present study, in a study, 10% garlic was added to butter and the results showed that it is not desirable in terms of sensory properties (Aydın and Tahmas Kahyaoğlu 2020). Another study found that the sensory scores of the ghee samples incorporated with 4.0, 6.0 and 8.0% orange peel powder extract were not in the acceptable range (Asha et al .…”
Section: Resultssupporting
confidence: 89%
“…2017a; 2017b; Mehdizadeh et al . 2019; Aydın and Tahmas Kahyaoğlu 2020; Simonenkova et al . 2021; Sadri Saeen et al .…”
Section: Introductionmentioning
confidence: 99%
“…The levels of calcium citrate, resistant starch, and garlic were defined based on previous works. And, in the case of garlic, sensory studies were also considered to define the level of addition (Aydın & Kahyaoğlu, 2020; Mohammed, 2017; Salinas et al., 2016; Suleria et al., 2015; Wang et al., 2013).…”
Section: Methodsmentioning
confidence: 99%
“…The altered phenolic compounds during BG processing are believed to be responsible for the superior suppression activity by neutralizing free radicals and chelating the metal ion [17]. Therefore, although G addition into meat products has been reported to decrease LOP formation [18], the higher phenolic concentration and antioxidant activity of the BG extract made it more effective in reducing the lipid oxidation rate, causing quality deterioration. Furthermore, the high antioxidant activity of the EBG group might be due to the extensive protection of antioxidant compounds during high-temperature exposure.…”
Section: Antioxidant Activity Total Phenolic Acid and Lipid Oxidationmentioning
confidence: 99%